Stimulus, expectations, desires and response strategies:The building blocks of nonlinear interaction dynamics - Dimitrios S. Dendrinos (Discrete Dynamics in Nature and Society)
Stimulus and response functions, as the fundamental blocks of nonlinear interaction dynamics, are analyzed and modeled here, under a variety of interaction strategies. The backbone of the suggested model is a simple iterative dynamical formulation: the magnitude of a signal sent at present is a function of a relevant signal sent—as well as of a signal received—in the past; in turn, a signal received at present is a function of a signal received—as well as of a signal sent—in the past; namely,Ss(n+1)=fs{Ss(n)Sr(n)}    and   Sr(n+1)=fr{Sr(n)Ss(n)}